2016
DOI: 10.1177/1947603516638901
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Associated Autologous Chondrocyte Implantation

Abstract: The significantly improved results on 3 scores after 15 years suggest that MACI represents a suitable treatment of local cartilage defects in the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 33 publications
2
56
2
Order By: Relevance
“…The study population 12 years after surgery involved a reduced follow-up rate due to limited patient participation and compliance as found to be associated with patient recruitment over long-term follow-up periods. 19,23,24 However, the extent of the current study population is equivalent to the previous studies of long-term matrixassisted ACI. 19,24 During the past years, different studies have been reporting successful long-term outcome of pACI as a cartilage repair procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population 12 years after surgery involved a reduced follow-up rate due to limited patient participation and compliance as found to be associated with patient recruitment over long-term follow-up periods. 19,23,24 However, the extent of the current study population is equivalent to the previous studies of long-term matrixassisted ACI. 19,24 During the past years, different studies have been reporting successful long-term outcome of pACI as a cartilage repair procedure.…”
Section: Discussionmentioning
confidence: 99%
“…19,23,24 However, the extent of the current study population is equivalent to the previous studies of long-term matrixassisted ACI. 19,24 During the past years, different studies have been reporting successful long-term outcome of pACI as a cartilage repair procedure. Follow-up of minimum 10 years showed survivorship of the repair site in 71% of the treated patients together with improved function in 75% 37 and satisfactory survival rates corresponding to significant clinical improvements could be reported up to 20 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of cartilage avascularity, low chondrocyte proliferative activity, and high extracellular matrix protein density, the intrinsic healing ability of the native cartilage tissue is limited and thus no tissue regeneration can be observed following cartilage injuries like chondral defects, microfractures, etc. Two common operative procedures (i.e., the autologous chondrocyte implantation, ACI, and the matrix-associated autologous chondrocyte implantation, MACI) used for cartilage repair exhibit limitations with regard to the cartilage defect size and geometry [ 1 , 3 , 4 , 5 , 6 , 7 ]. On the other hand, non-invasive topical administration via the injection of in situ forming cell-laden hydrogels could offer a promising alternative to the above operative procedures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While comprising the same scaffold associated potentials, the application of MACI also simplifies the surgery by omitting both the chondrocyte injection underneath a membrane and the watertight sealing to ensure chondrocyte containment within the lesion. While studies have demonstrated reduced rates of re-operation in membrane ACI compared with periosteal ACI, further comparative studies are needed to show superiority among these techniques [ 54 , 55 •, 56 ].…”
Section: Introductionmentioning
confidence: 99%